2007
DOI: 10.1007/s00423-007-0160-y
|View full text |Cite
|
Sign up to set email alerts
|

Organ dysfunction and long term outcome in secondary peritonitis

Abstract: Degree of organ dysfunction measured using SOFA score was the best predictor of hospital mortality in patients suffering from secondary peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
2
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 32 publications
3
23
2
6
Order By: Relevance
“…Only 58 % of patients in group 4 had leukocytosis, and of those with leukocytosis, the value was high. Some patients had normal values, and that response was expected because the inflammatory response in this series reached its peak after 73 h and because the instauration of sepsis would eventually lead to a decreased WBC count or even leukopenia [2,4,5,11,12,[22][23][24][25][26]. In studies using various diagnostic intervals, the incidence of leukocytosis varied from 78 to 88 % [2,3]; however, in one study using three different diagnostic intervals, the presence of leukocytosis increased along a prolonged time of symptom evolution [12].…”
Section: Discussionmentioning
confidence: 85%
“…Only 58 % of patients in group 4 had leukocytosis, and of those with leukocytosis, the value was high. Some patients had normal values, and that response was expected because the inflammatory response in this series reached its peak after 73 h and because the instauration of sepsis would eventually lead to a decreased WBC count or even leukopenia [2,4,5,11,12,[22][23][24][25][26]. In studies using various diagnostic intervals, the incidence of leukocytosis varied from 78 to 88 % [2,3]; however, in one study using three different diagnostic intervals, the presence of leukocytosis increased along a prolonged time of symptom evolution [12].…”
Section: Discussionmentioning
confidence: 85%
“…M Hynninen et al [8] in a series of 163 consecutive patients with secondary peritonitis, using APACHE II and SOFA scoring system, concluded that the degree of organ dysfunction measured using SOFA score was the best predictor of hospital mortality in patients suffering from secondary peritonitis.…”
Section: [6]mentioning
confidence: 99%
“…La mayoría de los pacientes en el grupo 1 (78%), tenían leucocitosis lo cual es esperable debido a la fase inicial del proceso inflamatorio [3][4][5][6]24 . En el grupo 4, 58% de los pacientes tuvieron un RL elevado, algunos pacientes tuvieron RL normales, esta respuesta también es esperable debido a que la respuesta inflamatoria seguida de la instauración de sepsis después de 72 h eventualmente lleva a la disminución del RL o a leucopenia 2,4,5,13,14,[24][25][26][27][28][29] . En estudios que utilizaron diferentes intervalos diagnósticos la incidencia de leucocitosis varió entre 78% y 88% 2,3 .…”
Section: Recuento De Leucocitosunclassified